Steroids Clinical Aspect - Abduljabbar, Hassan (IntechOpen, 2011)
Steroids: The basic science and clinical aspects covers the modern understanding and clinical use of steroids. The history of steroids is richly immersed and runs long and deep. The modern history of steroids started in the early 20th century, but its use has been traced back to ancient Greece. We start by describing the basic science of steroids. We then describe different clinical situations where steroids play an important role. We hope that this book will contribute further to the literature available about steroids and enables the reader to further understand this interesting and rapidly evolving science.